(Un)precedented: Reflecting on the Early Lessons of the COVID-19 Pandemic - Rector, Amanda (Maine Policy Review, 2021)
State Economist Amanda Rector reflects on her experience in the early days of the pandemic as she scrambled to find data to help state policymakers navigate this unprecedented event.
Keywords: Maine; COVID-19; pandemic; economic impacts